NEUTRALITY IN RELIGIOUS STUDY: pemikiran Peter Donovan - Mutia (Universitas Muhammadiyah Surabaya, 2024)
Peter Donovan is an academic who writes about neutrality in the study of religion. Neutrality in the study of religion can be interpreted as an attempt to understand another person's religion from the perspective of neutrality, and use the preferences of the person concerned to try to carry out reconstruction in and according to the other person's experience. This article aims to provide an understanding regarding the neutrality required in the study of religion and its relation to the field of religious politics. The method used in this research is library research. According to Donovan, there are three forms of neutrality in the study of religion, namely observer neutrality (researcher neutrality), participant neutrality (neutral participants), and role neutrality (neutral role). Peter Donovan defines neutrality in the study of religion as an effort to maintain an open, detached, objective, impartial, non-partisan and independent perspective in studying religion. Neutrality is necessary so that scholars can understand and appreciate the diversity of religious traditions and avoid imposing their own beliefs or values on the subject of their study.Keywords: Neutrality, Religious Studies, Politics